Pelatihan Splinting Gigi Goyang di RS Muhammadiyah Malang: Training on Splinting Loose Teeth at Muhammadiyah Hospital Malang - Indrawati, Dwi Wahyu; Manurung, Rizky Briliant Syah; Endarti, Esa Wahyu; Mukti, Ria Andriani; Manurung, Muhammad Rizky Akbar (International Consortium of Education and Culture Research Studies, 2025)
Tooth mobility is a common clinical manifestation of advanced periodontal disease that affects chewing function, aesthetics, and patients’ quality of life. Managing this condition requires a comprehensive approach, including stabilization procedures such as splinting and adjunctive therapies like chlorhexidine. To enhance healthcare providers' competencies, Muhammadiyah Hospital Malang conducted a clinical training workshop on the emergency management of mobile teeth. This workshop involved 30 dentists and covered theoretical knowledge, hands-on practice of splint fabrication using orthodontic wire and composite resin, application of chlorhexidine gel, and clinical case discussions. Evaluation through pre- and post-tests demonstrated a significant increase in participants’ knowledge (from 55% to 85%). The training not only improved participants’ technical skills but also strengthened interprofessional collaboration in managing complex periodontal cases. The outcomes underscore the importance of integrating similar programs into continuing education to support the improvement of dental healthcare quality and the implementation of higher education’s tridharma (education, research, and community service).